Luna : a novel - Peters, Julie Anne (Little, Brown, 2004)
Fifteen-year-old Regan's life, which has always revolved around keeping her older brother Liam's transsexuality a secret, changes when Liam decides to start the process of "transitioning" by first telling his family and friends that he is a girl who was born in a boy's body.